2006
DOI: 10.1103/physrevlett.97.243401
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Resonant Interatomic Coulombic Decay in Ne Dimers

Abstract: Properties of the interatomic Coulombic decay (ICD) process in Ne dimers have been obtained by tracking the formation of energetic Ne+ ions. The double photoionization cross section, deduced from the Ne+/Ne+ coincidence signal, is dominated by the ICD process and presents a threshold 280 meV below the atomic Ne+2s(-1) threshold. Rydberg excitation of a 2s electron in the dimer creates molecular Rydberg states whose Sigma and Pi symmetries have been resolved. These excited states decay by a resonant ICD process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 27 publications
1
42
1
Order By: Relevance
“…Other intermolecular or interatomic ionization mechanisms, for example electron impact ionization after photoionization, are typically one order of magnitude less probable. It occurs after ionization of an appropriate atomic shell (that is, an inner valence shell) [11][12][13] , after excitation [14][15][16] and especially as a terminal step after Auger decay [17][18][19] and therefore after ionization of the cluster compound with high-energy particles or photons. Most recently the main characteristic of ICD, ionization of nearest-neighbour molecules by energy transfer, was also seen in the core-hole relaxation of OH − dissolved in water 20 .…”
mentioning
confidence: 99%
“…Other intermolecular or interatomic ionization mechanisms, for example electron impact ionization after photoionization, are typically one order of magnitude less probable. It occurs after ionization of an appropriate atomic shell (that is, an inner valence shell) [11][12][13] , after excitation [14][15][16] and especially as a terminal step after Auger decay [17][18][19] and therefore after ionization of the cluster compound with high-energy particles or photons. Most recently the main characteristic of ICD, ionization of nearest-neighbour molecules by energy transfer, was also seen in the core-hole relaxation of OH − dissolved in water 20 .…”
mentioning
confidence: 99%
“…Since that time a wealth of experimental and theoretical studies have shown that ICD is a rather common decay path in nature, as it occurs almost everywhere in loosely bound matter. It has been proven to occur after a manifold of initial excitation schemes such as innervalence shell ionization, after Auger cascades [4,5], resonant excitation [6,7], shakeup ionization [8] and resonant Auger decay. ICD has also been observed in many systems as rare gas clusters [9], even on surfaces [10] and small water droplets [11,12].…”
mentioning
confidence: 99%
“…Upon core level photoionization, the created hole state undergoes ultrafast relaxation due to energy transfer to a neighbouring atom, and emits an electron from that neighbouring site. [11][12][13] The first successful attempt to measure non-protonated (H 2 O) n + (2≤n≤10) clusters was by Shinohara et al 14 who used the argon emission lines at 11.62 and 11.83 eV to ionize a mixed argon/water molecular beam. Since protonated water clusters and mixed (H 2 O) n Ar m + clusters were also observed, it was suggested that electron emission and Ar evaporation from these clusters led to the formation of the non-protonated species.…”
mentioning
confidence: 99%